Study on the Braking Efficiency and Optimal Design of the Drum Brake in Engineering Vehicle - Liu Li (Jixie chuandong)
For the issues of braking efficiency of the brake drum of engineering vehicle decline during use,taking the bi-directional-servo brake as research subjects,the calculation formula of brake braking efficiency is deduced.On this basis and combining with the actual object of key parameters and considering the interference of each parameter and manufacturing tolerances factors,the design of the model is optimized through robust optimization theory.Finally,the optimization model is validated through the finite element calculation.